Agrarkolonisation und Bodennutzungsprobleme im Oriente Ecuadors - Gerold, Gerhard; Lanfer, Norbert (ERDKUNDE, 2001)
Since fossil oil extraction and production began in the Oriente of Ecuador, the road infrastructure in the rainforest region of Coca has been developed intensively. Consequently, since 1964 continuous migration of day-labourers and small farmers from the Sierra and Costa and concomitant spontaneous colonisation of the Amazonian lowlands have taken place. According to satellite image analysis (Landsat-TM), rainforest clearing has been assessed at a rate of 4% p.a.. In the project region of Coca 80% of the main land use systems are dominated by cattle ranching and coffee plantations. The small scale farming systems using slash and mulch ignore the diverse land use potentials of the rainforest. Therefore rainforest conversion often takes place on soils with low fertility, resulting in low sustainable production and income. Soils with higher potential for crop production are often used only extensively; this is due to insufficient knowledge about intensification of land use systems, insufficient maintenance of permanent crops (coffee, cocoa) and lack of financial support or credit possibilities among small land owners. In relation to the relief differentiation the pedoecological analysis shows significant physical and chemical soil properties. Accordingly, potential of soil utilisation can be ranked as follows: Andic Eutropepts > Andic Dystropepts > Tropaquepts > Typic Udivitrands > Typic and Oxic Dystropepts. With respect to the major nutrients the nutrient contents of fresh leaves of the predominant plants (coffee, cocoa, banana, pasture grass) confirm the differentiation of soil fertility with widespread P-deficiency. Land use problems can be regionalized in relation to soil quality differentiation and plant nutrient analysis for a better land use planning. A long-term use seems to be possible, especially on the lower and higher plateau. The yield could be increased by a specific cultivation of the permanent cultures, the cultivation within agro-forest systems with increased agrobiodiversity, the deployment of café and cacao clonal, the rejuvenation of old plots of land, as well as fertilisation and, to a certain extent, mulching. An effective co-operation of the state departments in charge of regional development planning (INEFAN, INIAP and INDA), with a controlled colonisation policy, could offer the colonists a secure future and limit the quickly progressing conversion of the rainforest. An increased protection of the biodiversity and a reduction of the CO2-emissions in a global context is connected to this. But the reality looks different. The central government has not been paying much attention to the needs of the colonists. Moreover, the state department for regional development planning of the region is constantly lacking finances and personnel. The high fluctuation makes the problems even worse. Therefore, a change of the situation cannot be expected in the near future, although the colonists wish to make their lives and the economic situation better.